1998
DOI: 10.1159/000017930
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Milia, Steatocystoma multiplex and Eruptive Vellus Hair Cysts: Variable Expression of Multiple Pilosebaceous Cysts within an Affected Family

Abstract: Background: Steatocystoma multiplex (SM) and eruptive vellus hair cysts (EVHC) are conditions characterized by numerous cutaneous cysts with a clinical resemblance, such as age of onset, location, appearance of the lesions and mode of inheritance, but with distinctive histologic features. Recently, some authors have proposed that the two conditions are variants of one entity originating in the pilosebaceous duct, while others suggest that SM and EVHC are two distinct entities, on the basis of the different exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…Beş (%25) hastada eşlik eden başka bir hastalık (milia, steatokistoma multipleks, atopik dermatit, anhidrotik ektodermal displazi, diyabet ve kronik böbrek yetmezliği) izlendi. Hastaların 13'ünde (%65) lezyonların rengi deri renginden farklıydı, sadece birinde subjektif yakınma olarak kaşıntı mevcuttu 2,[6][7][8]13,14,16,[19][20][21][22][23][24][25][26] . Lezyonlardaki ağrı ve hassasiyete bizim olgumuz dışında rastlanılmadı.…”
Section: Discussionunclassified
“…Beş (%25) hastada eşlik eden başka bir hastalık (milia, steatokistoma multipleks, atopik dermatit, anhidrotik ektodermal displazi, diyabet ve kronik böbrek yetmezliği) izlendi. Hastaların 13'ünde (%65) lezyonların rengi deri renginden farklıydı, sadece birinde subjektif yakınma olarak kaşıntı mevcuttu 2,[6][7][8]13,14,16,[19][20][21][22][23][24][25][26] . Lezyonlardaki ağrı ve hassasiyete bizim olgumuz dışında rastlanılmadı.…”
Section: Discussionunclassified
“…Several authors have referred to the close relationship of between the EVHC and steatocystoma multiplex (SM). They suggested that both EVHC and SM may result from a cystic change of the pilosebaceous duct and so they may represent a spectrum of the same clinical entity 7,15 . Some case reports have described the simultaneous presence of EVHC and SM at one biopsy site 3,16,17 , or a hybrid cyst showing the combined histopathologic features of EVHC and SM 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Kumakiri et al 2 experienced a localized form of EVHC on the forehead and they called it the facial variant, and there has since been several case reports of such facial variants. Less than 15 cases of the so-called facial variant form of EVHC, which is localized exclusively on the face, have been reported [1][2][3][4][5][6][7][8][9][10] . There have also been a few cases on an unusual site such as the buttocks [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 at one biopsy site. Patrizi et al 5 suggested that milia and EVHC may represent an early sign of multiple pilosebaceous cystic disease and can be considered as a subtype of a multiple pilosebaceous cyst.…”
Section: Discussionmentioning
confidence: 99%